Polymorphism of TNF gene in acute coronary syndrome patients: data from the registries ORACLE I and ORACLE II - V. A. Brazhnik; L. О. Minushkina; A. О. Averkova; Е. A. Zubova; A. A. Rogozhina; М. A. Evdokimova; A. S. Galyavich; S. N. Tereshchenko; N. A. Koziolova; М. G. Glezer; А. V. Jagoda; О. I. Boeva; et al. (Российский кардиологический журнал, 2018)
Aim. To analyze possible association of the risk of adverse outcomes development in patients post acute coronary episode (ACS), with the polymorphism of gene TNF. Material and methods. To the study, patients included, that were under observation in 2 registry studies ORACLE I and II (Exacerbation of coronary heart disease: logic-probability ways of course prediction and treatment optimization). In overall, 2012 ACS patients assessed. Mean age 64,7±12,69 y.o. There were 1205 males (59,8%) and 807 females (40,2%). 741 patients (36,8%) included with ST elevation ACS, 1271 (63,2%) — with non-ST elevation ACS. Follow-up started at the 10th day from clinical stabilization. Clinical outcomes were gathered based on phone calls with the patients and their relatives, as during the outpatient office visits. Assessment of polymorphisms of gene TNF done with PCR.Results. In the assessed group, the frequency of alleles and gene TNF genotypes were measured: 18 patients carried genotype АА (0,9%), 561 patients — AG (279%), 1433 — GG (71,2%). In those with the allele А gene TNF, more commonly the episodes of SCD were noted (9,8% comparing to 6,6% of GG carriers, p<0,001); rate of non-cardiac death did not differ significantly (3,5% and 3,1%, respectively). There were no significant differences in the rate of fatal and non-fatal strokes, number of non-complicated cases of peripheral atherosclerosis. In the group of patients with allele A, there were more common the repeated ACS episodes (21,4% vs 12,8% in GG carriers, p<0,001). The rate of repeated after discharge interventions did not differ significantly. Independent factors for any adverse outcome (death, ACS, stroke, complicated atherosclerosis, repeated coronary interventions) were myocardial infarction (OR 1,235 (1,041-1,464)) and heart failure (OR 1,22 (1,02-1,44)) in anamnesis, decreased GFR (OR 1,04 (0,87-1,43)) and carriage of АА and AG gene TNF (OR 1,35 (1,14-1,60)). Conclusion. Carriage of the rare A allele of polymorphic marker G(-308)A gene TNF is associated with more common development of adverse outcomes in patients after exacerbation of CHD.